Assessment Of Adaptability And Stability Of Six Tunisian Cereal Genotypes Under Rainfed Conditions And At Two Semi Arid Environments - Ayed, Sourour; Othmani, Afef; Chaieb, Nadia; Bechrif, Salah; Rezgui, Mounir; Younes, Mongi Ben (European Scientific Journal, ESJ, 2016)
Three durum wheat (Nasr, Maâli and Salim), two bread wheat (Tahent and Utique) and two barley varieties (Manel and Kounouz) were assessed in two different semi arid locations under rainfed conditions in 2012-2013 growing season for yield related traits performances, stability and adaptability parameters. For determining adaptability and stability of genotypes, regression coefficient (bi) and variance of deviation from regression (S²di) are used. The evaluation was based on five agro-morphological traits: tiller number/plant, spike number/m2, plant number/m2, 1000 kernel weight and grain number/ spike. Variance analysis indicated a highly significant (p<0.05) effect of locations and genotypes for all studied traits. Also, the interaction between the genotypes and environments found to be highly significant (p<0.001) for all studied traits except the tiller number/plant. Analysis of stability showed that there were differences in stability performances among the genotypes for the traits tested. The unstability for spike number/m², plant number/m 2, 1000kernel weight and grain number/spike among the genotypes was originated from the high mean squares of deviation from regression. Analysis of AMMI model showed that Principal Components (PC) Analysis indicated that the two PCs explained 78.17% (PC1 = 41.51% and PC2 = 36.66%) of the total variation. Results showed that the group of genotypes Nasr, Tahent, Kounouz and Manel having wide adaptability and could be recommended for cultivation across diverse environments.